Research on the Cognitive Degree of Pre-Service High School Mathematics Teachers for Intuitive Imagination Literacy - Meng, Yanyun; Sun, Haojie; Zhou, Xun; Yang, Zezhong (Asian Journal of Contemporary Education, 2022)
Currently, many relevant problems about intuitive imagination literacy have been studied except the cognitive degree of pre-service high school mathematics teachers about it. To address this gap, this study investigates 51 pre-service high school mathematics teachers. Results showed that: 1. The cognitive scope of them about intuitive imagination literacy is not extensive, more than half of the content of intuitive imagination literacy is not recognized; 2. The cognition of many pre-service teachers is not deep or comprehensive and concentrates at a lower level; 3. The cognition of many pre-service teachers for many aspects of intuitive imagination literacy is not very clear. It is suggested that: 1. experts and teachers who are responsible for educating teachers should pay more attention to intuitive imagination literacy and add relevant courses; 2. pre-service high school mathematics teachers should understand the content of intuitive imagination literacy comprehensively and deeply, and clarify relevant statements.